2017
DOI: 10.1021/acs.jpcc.7b00760
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Conductive Oxide Layer and Hole Selective Layer Free Back-Contacted Hybrid Perovskite Solar Cell

Abstract: Back-contacted architectures have been under intensive investigation for that transparent conductive oxide (TCO) less solar cells (SCs) can be easily realized which avoid the transmission loss of light caused by TCO, typically comprised in conventional solar cells. Here, network-like porous Ti was first utilized as the back-contacted electrode, and a new design allows for a novel backcontacted hybrid perovskite SC without TCO and hole selective layer, which shows a power output of 3.88% with long-term stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…15,16,114 MA-J: What has been done so far with IBC perovskite solar cells? MA: There have been only a few reports on IBC solar cells employing perovskites, some focussed on device optimization [114][115][116][117] and others focussed on understanding the device physics of perovskite materials 15,16 . In addition to the advantages mentioned above, IBC devices have been proposed by Bach's group as a potential solution to overcome issues related to pin holes (i.e.…”
Section: Interdigitated Back-contact Solar Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16,114 MA-J: What has been done so far with IBC perovskite solar cells? MA: There have been only a few reports on IBC solar cells employing perovskites, some focussed on device optimization [114][115][116][117] and others focussed on understanding the device physics of perovskite materials 15,16 . In addition to the advantages mentioned above, IBC devices have been proposed by Bach's group as a potential solution to overcome issues related to pin holes (i.e.…”
Section: Interdigitated Back-contact Solar Cellsmentioning
confidence: 99%
“…114 The drawback of this architecture is that it involves rather complicated photolithography and multiple deposition steps, which is a bottleneck for large scale production. 116 Hu et al reported a different back-contact perovskite solar cell architecture achieving 3.9% PCE. 116 The authors do not employ any TCO nor any hole selective layer.…”
Section: Interdigitated Back-contact Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Back-contact architectures have the advantage that they can reduce parasitic absorption losses that otherwise occur in the device substrate, in TCO layers, or in other charge-transport layers that are used to extract photogenerated charges. [2][3][4] Ensuring that the active layer is directly exposed to the illumination source reduces reflection losses that otherwise occur in a conventional planar PV device, and also allow anti-reflective strategies to be directly engineered onto the active layer. Backcontact designs also enable the use of non-transparent electrodes, including highly conductive metals.…”
Section: Introductionmentioning
confidence: 99%
“…Backcontact designs also enable the use of non-transparent electrodes, including highly conductive metals. This gives back-contact PV devices an inherent advantage, as the loss of photogenerated charges due to the series resistance of the electrodes can be a significant issue in large-area solar modules, as the TCOs [2][3][4] typically used often have a sheet resistance of 10-20 O per square. Thus replacing TCOs with metallic layers whilst using backcontact architecture presents -in principle -a method to both maximise light collection and minimise parasitic resistance losses in PV devices.…”
Section: Introductionmentioning
confidence: 99%